2018
DOI: 10.1093/jpids/piy090
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Pathogens in Children 1 Month to 5 Years of Age Presenting With Undifferentiated Acute Respiratory Distress in 2 District-Level Hospitals in Ghana

Abstract: Ghanaian children (2176) aged <5 years who presented with undifferentiated acute respiratory distress were tested for respiratory pathogens using a BioFire FilmArray polymerase chain reaction assay. Rhinovirus and/or enterovirus was detected in 36% of the assays, respiratory syncytial virus in 11%, and parainfluenza in 7%. Respiratory syncytial virus and metapneumovirus were detected more frequently in the rainy season than in the dry season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Following closely were rhinovirus at 32% and influenza A at 20%. While respiratory syncytial virus is globally recognized as a primary cause of hospitalization [24,25] and a significant contributor to child mortality [24,25], it does not always emerge as the most identified virus in respiratory infections among children [19,[26][27][28]. Indeed, various epidemiological studies on pediatric patients have indicated that other viruses, particularly human rhinovirus/enterovirus, may be more commonly associated with children's respiratory infections [19,26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following closely were rhinovirus at 32% and influenza A at 20%. While respiratory syncytial virus is globally recognized as a primary cause of hospitalization [24,25] and a significant contributor to child mortality [24,25], it does not always emerge as the most identified virus in respiratory infections among children [19,[26][27][28]. Indeed, various epidemiological studies on pediatric patients have indicated that other viruses, particularly human rhinovirus/enterovirus, may be more commonly associated with children's respiratory infections [19,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al [26] conducted a study (2014)(2015) showing that HRV/EV was the most detected virus (RSV only 11%).…”
Section: Discussionmentioning
confidence: 99%